Karakterisasi Senyawa Metabolit Daun Sirih (Piper betle L.) Berdasarkan Studi Literatur serta Potensi Bioaktifnya dalam Bidang Kesehatan - Tamimil Hasanah; Ardi Mustakim (MUARA KESEHATAN : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Betel leaf (Piper betle L.) is a herbal plant that has long been used in traditional medicine and is known to contain various secondary metabolites with potential bioactive effects on human health. This study aims to characterize the metabolite compounds of betel leaves and to review their bioactive potential based on a literature study. The research method employed was a literature review by analyzing relevant national and international scientific articles published in reputable and indexed journals. The selected literature focused on the types of secondary metabolites, analytical methods used, and reported bioactivities. The results of the literature synthesis indicate that betel leaves contain several metabolite compounds such as flavonoids, phenolics, alkaloids, tannins, saponins, and essential oils. These compounds have been reported to exhibit various bioactivities, including antibacterial, antioxidant, anti-inflammatory, and antifungal activities. Based on the literature review, betel leaves have significant potential to be developed as a natural source for health-related applications. This study is expected to provide a scientific basis for further research on the utilization of betel leaves as natural therapeutic agents